Method for improving high-temperature oxidation resistance of NiCoCrAlY cladding layer

The NiCoCrAlY cladding layer is processed through laser impact technology to adjust the stress distribution and increase crystal defects, solving the problem of oxide film peeling of the coating in a high-temperature environment, and significantly improving its resistance to high-temperature oxidation.

CN119843273APending Publication Date: 2025-04-18NANCHANG HANGKONG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510089395.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing MCrAlY coating is prone to oxide film falling off in high temperature environments, affecting its anti-high temperature oxidation performance.

Method used

The NiCoCrAlY cladding is processed by laser impact technology, adjusting the residual stress distribution on its surface, and increasing crystal defects (dislocations), thereby improving the coating's resistance to high-temperature oxidation.

Benefits of technology

The oxide film grown in a high-temperature environment with the NiCoCrAlY coating processed by laser shock technology has good anti-flaking properties, which significantly improves the anti-high-temperature oxidation properties of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843273A_ABST
    Figure CN119843273A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving high-temperature oxidation resistance of a NiCoCrAlY cladding layer. The method comprises the following steps: S1, cladding a NiCoCrAlY protective coating on GH4169 by adopting coaxial powder feeding laser cladding equipment; s2, a black adhesive tape is arranged on the NiCoCrAlY cladding layer to serve as an absorption layer, and flowing water is arranged to serve as a restraint layer; carrying out single laser shock treatment on the NiCoCrAlY cladding layer by adopting a nanosecond laser; and S3, the treated NiCoCrAlY cladding layer is put into acetone to be subjected to soaking treatment. According to the NiCoCrAlY protective coating prepared through the method, a compact and continuous protective oxidation film grows under the extremely short high-temperature oxidation time, and the oxidation film has the advantage of being not prone to falling off, so that the high-temperature oxidation resistance of the coating is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-temperature protective coatings and surface modification, and in particular relates to a method for improving the high-temperature oxidation resistance of a NiCoCrAlY cladding layer. Background Art

[0002] MCrAlY (M = Ni, Co or NiCo) is an intermetallic compound material with excellent high-temperature oxidation resistance and heat corrosion resistance. It has been widely used in thermal barrier coatings for gas turbines and aircraft engines. At present, the preparation methods of MCrAlY coatings mainly adopt atmospheric plasma spraying, arc ion plating, supersonic flame spraying and other technologies. However, these preparation technologies have some defects to varying degrees. For example, the coatings prepared by atmospheric plasma spraying technology have large surface roughness and the presence of layered oxides and large porosity in the coatings, which makes it difficult to form a dense and continuous Al2O3 protective film, which is extremely unfavorable to the high-temperature service performance of the coatings. In recent years, laser cladding technology has been applied to the preparation of high-temperature resistant protective coatings and has achieved good results. The principle is: a high-energy laser beam melts the alloy powder and the substrate surface at the same time, and the alloy powder solidifies rapidly, and finally forms a coating metallurgically bonded to the substrate. The coating prepared by laser cladding technology has the advantages of dense structure and fine grains. However, since the laser cladding process involves rapid cooling and heating, this will lead to uneven stress distribution in the coating. This defect will make it easy for the oxide film grown on the sample to fall off when it serves in a subsequent high-temperature environment, affecting the coating's resistance to high-temperature oxidation.

[0003] Laser shock technology is an advanced surface treatment technology that has been widely used in recent years to improve the wear resistance and high temperature resistance of alloys or coatings. This technology uses a high-energy laser beam to act on the absorption layer, causing the absorption layer to explode and evaporate to generate a plasma shock wave. The shock wave causes severe plastic deformation on the surface of the sample and produces a large number of crystal defects (dislocations, etc.). These crystal defects can promote short-circuit diffusion, so that when the high-temperature alloy is in service in a high-temperature environment, the diffusion rate of alloy elements increases, thereby accelerating the generation rate of the oxide film. And because the high-temperature and high-pressure plasma acts on the surface, the residual stress distribution on the surface of the sample can be changed to a certain extent.

[0004] In summary, it is feasible to apply laser shock surface modification technology to improve the high-temperature oxidation resistance of coatings.

[0005] It should be noted that the information disclosed in this background technology is only intended to increase the understanding of the overall background of the present invention and to understand the background in which the inventor came up with the inventive concept, and should not be regarded as an admission or any form of implication that all the information constitutes prior art already known to those skilled in the art. Summary of the invention

[0006] In view of this, in order to solve the technical problems existing in the technical background, the present invention proposes a method for improving the high-temperature oxidation resistance of the NiCoCrAlY cladding layer. The method uses laser shock technology to adjust the residual stress distribution on the surface of the cladding layer on the one hand, and to produce a certain number of crystal defects (dislocations) in the coating on the other hand, thereby effectively improving the high-temperature oxidation resistance of the coating.

[0007] The technical solutions adopted are: A method for improving the high temperature oxidation resistance of a NiCoCrAlY cladding layer comprises the following steps: S1. Coaxial powder feeding laser cladding equipment was used to clad NiCoCrAlY protective coating on GH4169; S2. Setting a black tape as an absorption layer and flowing water as a constraint layer on the NiCoCrAlY cladding layer; performing a single laser shock treatment on the NiCoCrAlY cladding layer using a nanosecond laser; S3. Immerse the treated NiCoCrAlY cladding layer in acetone.

[0008] Further, in step S1, the parameters of laser cladding performed by the coaxial powder feeding laser cladding equipment are: The fixed laser scanning speed is 600mm / min, the protective gas flow rate is 15L / min, the spot overlap rate is 50%, the laser power is 550W, the powder feeding gas flow rate is 4L / min, and the powder feeding disk speed is 0.3r / min.

[0009] Furthermore, the protective gas is argon.

[0010] Furthermore, in step S2, the parameters of the nanosecond laser for laser shock peening are: The spot diameter is 2 mm, the pulse width is 1064 nm, the pulse energy is 10 J, and the overlap rate is 50%.

[0011] Furthermore, before step S1, the method further includes S01. performing a drying pretreatment on the surface of the high-temperature alloy GH4169 substrate.

[0012] Furthermore, in S01, the surface of the high-temperature alloy GH4169 substrate is dried and pretreated by grinding the substrate with 800-grit sandpaper, then putting it into alcohol for ultrasonic alcohol cleaning, and then putting it into a drying oven set at a temperature of 100° C. for drying.

[0013] Furthermore, before step S1, it also includes S02. Drying pretreatment of the cladding powder NiCoCrAlY powder.

[0014] Furthermore, S02. The cladding powder NiCoCrAlY powder is dried pre-treated by placing the NiCoCrAlY powder in a drying oven set at a temperature of 120° C. for drying.

[0015] The beneficial effects of the present invention are: The present invention combines coaxial powder feeding laser cladding and laser shock strengthening to prepare the NiCoCrAlY cladding layer, generates high-temperature and high-pressure plasma shock waves through nanosecond laser induction, improves the stress distribution on the coating surface, and increases the number of crystal defects inside the coating.

[0016] The present invention applies coaxial powder feeding laser cladding technology and laser shock peening technology to the preparation of NiCoCrAlY coating, and prepares a coating with good bonding performance with the substrate and low dilution rate. In addition, the TGO grown by the cladding layer after laser shock treatment in a high temperature environment of 1100℃ has good anti-stripping performance, which effectively improves the high temperature oxidation resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the information diagram related to NiCoCrAlY cladding layer; Figure 2 Schematic diagram of the laser shock peening process; Figure 3 XRD diagram of NiCoCrAlY cladding layer before and after laser shock treatment; Figure 4 The surface morphology of NiCoCrAlY cladding layer before and after laser shock after high temperature oxidation for 10 minutes; Figure 5 The cross-sectional morphology of the TGO cladding layer before and after laser shock after high-temperature oxidation for 10 minutes; Figure 6 The cross-sectional morphology and EDS images of the cladding layer before and after impact after high temperature oxidation for 225 hours; Figure 7 The macroscopic morphology of the cladding layer after 300 hours of oxidation before and after laser shock and the SEM and EDS images of the detached area. DETAILED DESCRIPTION

[0018] The present invention is described in detail below through specific examples, but the use and purpose of these exemplary embodiments are only used to illustrate the present invention, and do not constitute any form of limitation on the actual protection scope of the present invention, and do not limit the protection scope of the present invention to these. Example 1

[0019] A method for improving the high temperature oxidation resistance of the NiCoCrAlY cladding layer in this embodiment is achieved by the following steps: 1) Preparation of substrate and powder for cladding: Grind the high-temperature alloy GH4169 with 800-grit sandpaper, then put it into anhydrous ethanol for ultrasonic cleaning to remove surface impurities, and finally put the substrate material into a drying oven at 100°C for 1-2 hours.

[0020] 2) The cladding powder is then dried by placing the NiCoCrAlY powder in a drying oven set at 120 degrees for 5-6 hours. The powder and matrix composition used are shown in Table 1.

[0021] Table 1 High temperature alloy GH4169 and NiCoCrAlY powder composition ratio (weight percentage) Elements (wt.%) Ni Al Cr Co Y Fe Mo Nb C Inconel 718 (GH4169) Bal 0.84 17.67 - - 18.66 5.01 5.84 0.06 NiCoCrAlY Bal 13 18 24 0.6 - - - - 3) The NiCoCrAlY protective coating was clad on GH4169 using Nanjing Zhongke Yuchen LDM-8060 coaxial powder feeding laser cladding equipment; the specific laser cladding process parameters include: laser power 530W, spot diameter 2mm, powder feeding rate 0.35r / min, laser scanning speed 600mm / min, overlap rate 50%.

[0022] The laser cladding process parameters used were obtained through orthogonal experiments. The specific implementation method was to fix the laser scanning speed at 600mm / min, the shielding gas flow rate at 15L / min, and the spot overlap rate at 50%. The optimal combination of laser power, powder feeding gas flow rate, and powder feeding disk speed was explored. The specific parameters are shown in Table 2. According to the results of the prepared cladding layer dilution rate, the optimal parameter combination is 550W laser power, 4L / min powder feeding gas flow rate, and 0.3r / min powder feeding disk speed. The element distribution of the optimal cladding layer is as follows: Figure 1 (d) as shown; Table 2 Orthogonal experimental parameters of laser cladding parameters Sample No. Laser power(W) Powder disk speed (R / min) Powder feeding gas flow rate (L / min) <![CDATA[Energy density (J / mm 2 )]]> 1 500 0.25 2 27.5 2 500 0.3 3 27.5 3 500 0.35 4 27.5 4 550 0.3 3 30 5 550 0.3 4 30 6 550 0.35 2 30 7 600 0.35 4 32.5 8 600 0.25 2 32.5 9 600 0.3 3 32.5 4) Black tape is pasted on the surface of the prepared NiCoCrAlY cladding layer as an absorption layer, and flowing water is used as a constraint layer. The cladding layer is subjected to laser shock surface modification by a nanosecond pulse laser. The specific parameters are as follows: spot diameter 2 mm, pulse width 1064 nm, pulse energy 10 J, overlap rate 50%, and the specific scanning path is as follows: Figure 2 , the cladding layer after laser shock treatment.

[0023] 5) The treated NiCoCrAlY cladding layer is immersed in acetone to remove the black tape constraint layer remaining on the surface.

[0024] Performance and characterization test of NiCoCrAlY cladding layer before and after laser shock treatment: (1) X-ray diffraction test (XRD) The phase analysis of NiCoCrAlY cladding layer before and after laser shock treatment was carried out by X-ray diffractometer, and the specific parameters adopted were as follows: scanning speed 10° / min, scanning angle 2 ranging from 20° to 80°. The specific results are shown in Figure 3 As shown in the figure, it can be clearly found that the diffraction peak shifts to a low angle, which indicates that the excessive pulse energy of the laser shock causes severe plastic deformation on the surface of the cladding layer, changing the surface stress distribution to be mainly tensile stress. At the same time, it can be found that the half-peak width of the (111) and (110) diffraction peaks increases significantly after laser shock treatment, indicating that the microscopic crystal defects inside the coating increase significantly after shock surface modification.

[0025] (2) Scanning electron microscope test (SEM) of cladding layer The laser cladding layer was observed using a FEI scanning electron microscope. Figure 1 The cross-sectional SEM image of the NiCoCrAlY cladding layer prepared by the present invention after being etched by aqua regia shows that the coating is dense and continuous without obvious cracks or holes, and the coating is composed of a network and dendritic structure. Figure 1 It can be found that the elements of the coating are evenly distributed, there is no large amount of matrix Fe element, and the element interdiffusion area is only about 50μm.

[0026] (3) High temperature oxidation performance test The laser shock surface modified samples and the original samples were placed in a box furnace set at 1100°C for constant temperature oxidation experiments. The high temperature oxidation experiment results show that: in the initial oxidation period (10 minutes), the combined Figure 4 and Figure 5 The surface and cross-sectional morphology of the coating shown in the figure show that a dense and continuous protective oxide film quickly grows on the surface of the cladding layer after laser shock surface modification, while the surface of the original cladding layer is mainly composed of needle-shaped oxides such as -Al2O3. Figure 6 As shown in the figure, when the isothermal oxidation experiment was carried out for 225 hours, the cladding layers before and after laser shock surface modification grew a continuous and dense Al2O3 protective oxide film. Unlike the original cladding layer, there are some mixed oxides on the surface of the cladding layer after laser shock surface modification. This shows that laser shock increases the diffusion rate of alloy elements in the early stage of high-temperature oxidation, allowing more alloy elements such as Ni and Cr to participate in the initial oxidation. With the increase of exposure time in the high-temperature environment, a certain degree of growth of mixed oxides composed of Ni, Cr, and Al appears on the surface of the oxide film. Figure 7 The figure shows the surface of the oxide film after the coating was oxidized for 300 hours. It can be found that the oxide film on the surface of the original NiCoCrAlY cladding layer has fallen off in a large area, while the oxide film on the surface of the coating after laser shock treatment is intact and has not fallen off in a large area.

[0027] In summary, the NiCoCrAlY protective coating prepared in the present invention grows a dense and continuous protective oxide film in a very short high-temperature oxidation time, and the oxide film is not easy to fall off, which effectively improves the high-temperature oxidation resistance of the coating.

[0028] The high temperature oxidation resistance of the coating prepared by combining the laser cladding technology with the laser shock surface modification process of the present invention is significantly improved.

[0029] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for improving the high temperature oxidation resistance of a NiCoCrAlY cladding layer, characterized in that: The steps include: S1. Coaxial powder feeding laser cladding equipment was used to clad NiCoCrAlY protective coating on GH4169; S2. Setting a black tape as an absorption layer and flowing water as a constraint layer on the NiCoCrAlY cladding layer; performing a single laser shock treatment on the NiCoCrAlY cladding layer using a nanosecond laser; S3. Immerse the treated NiCoCrAlY cladding layer in acetone.

2. The method for improving the high temperature oxidation resistance of the NiCoCrAlY cladding layer according to claim 1, characterized in that: In step S1, the parameters of laser cladding performed by the coaxial powder feeding laser cladding equipment are: The fixed laser scanning speed is 600mm / min, the protective gas flow rate is 15L / min, the spot overlap rate is 50%, the laser power is 550W, the powder feeding gas flow rate is 4L / min, and the powder feeding disk speed is 0.3r / min.

3. The method for improving the high temperature oxidation resistance of the NiCoCrAlY cladding layer according to claim 2, characterized in that: The protective gas is argon.

4. The method for improving the high temperature oxidation resistance of the NiCoCrAlY cladding layer according to claim 1, characterized in that: In step S2, the parameters of the nanosecond laser for laser shock peening are: The spot diameter is 2 mm, the pulse width is 1064 nm, the pulse energy is 10 J, and the overlap rate is 50%.

5. The method for improving the high temperature oxidation resistance of the NiCoCrAlY cladding layer according to claim 1, characterized in that: Before step S1, the method further includes step S01. performing a drying pretreatment on the surface of the high temperature alloy GH4169 substrate.

6. The method for improving the high temperature oxidation resistance of the NiCoCrAlY cladding layer according to claim 5, characterized in that: In S01, the surface of the high-temperature alloy GH4169 substrate is dried and pretreated by grinding the substrate with 800-grit sandpaper, then putting it into alcohol for ultrasonic alcohol cleaning, and then putting it into a drying oven set at a temperature of 100°C for drying.

7. The method for improving the high temperature oxidation resistance of the NiCoCrAlY cladding layer according to claim 1, characterized in that: Before step S1, the method further includes step S02: performing drying pretreatment on the cladding powder NiCoCrAlY powder.

8. The method for improving the high temperature oxidation resistance of the NiCoCrAlY cladding layer according to claim 7, characterized in that: S02. The cladding powder NiCoCrAlY powder is dried pre-treated by placing the NiCoCrAlY powder in a drying oven set at a temperature of 120° C. for drying.